2014
DOI: 10.1016/j.ijpara.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Excreted/secreted Schistosoma mansoni venom allergen-like 9 (SmVAL9) modulates host extracellular matrix remodelling gene expression

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 72 publications
1
40
0
Order By: Relevance
“…Whole parasite preparations of S. mansoni, particularly the egg antigens, are known to induce Th2 responses . We sought to validate our protocol by examining immune responses to crude parasite preparations of AWA and SEA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whole parasite preparations of S. mansoni, particularly the egg antigens, are known to induce Th2 responses . We sought to validate our protocol by examining immune responses to crude parasite preparations of AWA and SEA.…”
Section: Resultsmentioning
confidence: 99%
“…For rSmTSP6 and rSmTSP7, 84 and 78 amino acids were expressed, representing the extracellular loop 2 of these proteins, respectively, as defined by TMHMM2.0 software . About 106‐189 amino acid of rSmTSP6 and 108‐185 amino acid of rSmTSP7 were expressed using the same vector, expression parameters and purification methods as rSmLy6A and B . Endotoxin contamination of the recombinant antigens was determined by Limulus amebocyte lysate (LAL) assay using the Pierce LAL chromogenic endotoxin quantitation kit (Thermo Fisher, Pittsburgh, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SmVALs can be divided into two groups and exhibit various gene expression patterns throughout the entire life-cycle, including genes exclusively expressed in stages involved in intermediate host invasion or definitive host invasion and ubiquitously expressed genes [32]. Because of their potential functional classification, expression patterns and localization, SmVALs have been proposed as potential drug targets and vaccine candidates, and some members have been well characterized recently [66][67][68]. For instance, Farias et al have demonstrated that SmVAL4 and SmVAL26 stimulate differential allergic responses in a murine model of airway inflammation [66]; and in a recent study, egg-derived SmVAL9 was found to carry an N-linked glycan containing a schistosome-specific difucosyl element and function as an immunogenic target during chronic murine schistosomiasis [68].…”
Section: Phylogenetic Analysis and Global Expression Profiling Of Thementioning
confidence: 99%
“…Because of their potential functional classification, expression patterns and localization, SmVALs have been proposed as potential drug targets and vaccine candidates, and some members have been well characterized recently [66][67][68]. For instance, Farias et al have demonstrated that SmVAL4 and SmVAL26 stimulate differential allergic responses in a murine model of airway inflammation [66]; and in a recent study, egg-derived SmVAL9 was found to carry an N-linked glycan containing a schistosome-specific difucosyl element and function as an immunogenic target during chronic murine schistosomiasis [68]. In our study, 20 non-redundant S. japonicum venom-allergen-like protein (SjVAL) genes were identified in the genome.…”
Section: Phylogenetic Analysis and Global Expression Profiling Of Thementioning
confidence: 99%